Political connection as a moderator in the relationship between green innovation and firm value: The mediating role of financial performance in Indonesia - Rochmah, Siti; Emha, Putri Aulia; Syofrin, Nadila Deryza (Privietlab, 2026)
This study aims to analyze the influence of green innovation on the value of companies with financial performance as mediators and political connections as moderation variables in the energy sector listed on the Indonesia Stock Exchange for the period 2020–2024. Using the purposive sampling method of 50 observations, the data was analyzed through Partial Least Square (PLS-SEM) with the help of SmartPLS 4.0. The results of the study revealed that green innovation had a significant positive effect on financial performance (β=0.252; p=0.031), but has no direct effect on the company's value (β=0.051; p=0.681). Financial performance was also found to fail to mediate the relationship (β=0.017; p=0.672), indicating that the capital market has not appreciated internal efficiency based on the environment independently. The most crucial finding is that political connections act as the main differentiating factor. Green innovation significantly improves financial performance (β=0.304; p=0.050) and company value (β=0.244; p=0.042) only in entities with political networks. The implications of this study confirm that in emerging markets, the technical capabilities of innovation must synergize with political institutional assets to achieve optimal market performance; therefore, the government needs to design a more transparent and inclusive energy transition incentive scheme for all industry players.